Pengaruh Media Pembelajaran Colored Stick Pada Materi Penjumlahan dan Pengurangan Bilangan Bulat Terhadap Hasil Belajar Siswa Kelas IV Sekolah Dasar Negeri 15 Sungai Pinyuh - Mukmin, Mukmin; Risdiana Andika Fatmawati; Siti Nur Asmah (PT. ALHAFI BERKAH INDONESIA, 2024)
This study aims to determine the Effect of Colored Stick Learning Media on Addition and Subtraction of Integers on Learning Outcomes of Grade IV Students at SDN 15 Sungai Pinyuh. The exploration technique utilized is the trial strategy, while the examination configuration utilized is pre-exploratory plan. The autonomous variable (X) in this study is the impact of shaded stick learning media, while the reliant variable (Y) is learning results. The populace remembered for this review were 4th grade understudies at SDN 15 Sungai Pinyuh. There were a total of 36 students, with 14 female and 22 male students. The example in this review was 4th grade understudies at SDN 15 Sungai Pinyuh. The technique used for determining the experimental class uses the data collection technique of learning achievement tests. In data collection using tests and documentation. Hypothesis testing uses the formula t-test (Paired sample t-test) which is preceded by a prerequisite analysis test, namely the normality test. The results showed that there were significant differences in student learning outcomes before and after using colored stick learning media. This is indicated by the results of the normality test data obtained, namely the significant value for the pretest, namely 0.132 > 0.05 and the significant value for the posttest, namely 0.069 > 0.05, the decision criterion, namely H0, is accepted. Furthermore, based on the results of the Paired sample t test, the result is a significant value of 0.000 <0.05, so it can be concluded that H0 is rejected and Ha is accepted. So it can be concluded that there is an influence of the Colored Stick learning media on the learning outcomes of class IV students at SDN 15 Sungai Pinyuh.